Sustainability and valuation of intangible cultural heritage in Manabí: strengthening strategies - Vera Solorzano, José Darío (2024)
Intangible cultural heritage plays a significant social role in the modern world since it links a people with its history, customs and traditions. This exploration aimed to prepare a sustainability study to strengthen the ICH in the northern area of Manabí, Ecuador, with a mixed, nonexperimental and non-exploratory approach. Analysis techniques and instruments were applied for data collection, where the tourist’s assessment regarding the PCI of the study area was obtained. Eighty-five intangible cultural expressions characterised the study area; interviews were applied to actors and managers involved in the artistic work of their localities. Finally, strategies were designed to strengthen cultural organisations to form cultural public policies, focusing on safeguarding and legal rights protection and raising awareness among local communities.